Randomized controlled trial of irinotecan drug‐eluting beads with simultaneous FOLFOX and bevacizumab for patients with unresectable colorectal liver‐limited metastasis. Issue 20 (6th July 2015) - Martin, Robert C. G.; Scoggins, Charles R.; Schreeder, Marshall; Rilling, William S.; Laing, Christopher J.; Tatum, Clifton M.; Kelly, Lawrence R.; Garcia‐Monaco, Ricardo D.; Sharma, Vivek R.; Crocenzi, Todd S.; Strasberg, Steven M.
<x xml:space="preserve">Abstract</x> BACKGROUND Reports have demonstrated the superior activity of combining both irinotecan and oxaliplatin (FOLFOXIRI) therapy. An option for gaining similar benefits with less toxicity would be the administration of irinotecan through a hepatic artery approach. The aim of this study was to assess the response and adverse event rates for irinotecan drug‐eluting beads (DEBIRI) with folinic acid, 5‐fluorouracil, and oxaliplatin (FOLFOX) and bevacizumab as a first‐line treatment for unresectable colorectal liver metastasis. METHODS Patients with colorectal liver metastases were randomly assigned to modified FOLFOX (mFOLFOX) and bevacizumab or mFOLFOX6, bevacizumab, and DEBIRI (FOLFOX‐DEBIRI). The primary endpoint was the response rate. The secondary endpoints were adverse events, the rate of conversion to resection, and progression‐free survival. RESULTS The intention‐to‐treat population comprised 70 patients: 10 patients in the pilot and then 30 patients randomly assigned to the FOLFOX‐DEBIRI arm and 30 patients randomly assigned to the FOLFOX/bevacizumab arm. The 2 groups were similar with respect to the extent of liver involvement (30% vs 30%), but a greater percentage of patients in the FOLFOX‐DEBIRI arm had an Eastern Cooperative Oncology Group performance status of 1 or 2 (57% vs 31%) and extrahepatic disease (56% vs 32%, P = .02). The median numbers of chemotherapy cycles were similar (10 vs 9), and there were similar rates of grade 3/4 adverse events (54% for the FOLFOX‐DEBIRI group vs 46% for the FOLFOX/bevacizumab group). The overall response rate was significantly greater in the FOLFOX‐DEBIRI arm versus the FOLFOX/bevacizumab arm at 2 (78% vs 54%, P = .02), 4 (95% vs 70%, P = .03), and 6 months (76% vs 60%, P = .05). There was significantly more downsizing to resection in the FOLFOX‐DEBIRI arm versus the FOLFOX/bevacizumab arm (35% vs 16%, P = .05), and there was improved median progression‐free survival (15.3 vs 7.6 months). CONCLUSIONS The simultaneous administration of mFOLFOX6 (with or without bevacizumab) and DEBIRI through the hepatic artery (FOLFOX‐DEBIRI) is safe and does not cause treatment delays or increase the systemic toxicity of chemotherapy. This strategy leads to improved overall response rates, improved hepatic progression‐free survival, and more durable overall progression‐free survival in patients downsized to resection. Cancer 2015. © 2015 American Cancer Society. Cancer 2015;121:3649–3658. © 2015 American Cancer Society.